Tingkat Kondisi Fisik Pemain Futsal Putra di MA Negeri 1 Mataram Tahun 2026 - Muhammad Bakhtiar Misbah; Dadang Warta Chandra Wira Kesuma; Indri Susilawati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Physical condition is a key factor determining futsal players' performance, as matches are played at high intensity and demand optimal aerobic and anaerobic capabilities. However, the physical condition profiles of school-level futsal athletes are rarely comprehensively evaluated to serve as a basis for training program design. This study aims to describe the physical condition levels of male futsal players at MAN 1 Mataram. A quantitative approach with a descriptive design was employed. The sample consisted of 16 players selected using total sampling. Data collection involved the Multistage Fitness Test (MFT) to measure VO₂Max, a 30-meter sprint test, the Illinois agility test, a 60-second push-up test, and a vertical jump test. Data were analyzed using descriptive statistics specifically mean values ​​and percentages based on the norms for each test instrument. The results showed that leg muscle explosive power averaged 51.56 cm (predominantly "good" category), sprint speed averaged 4.15 seconds ("good" category), agility averaged 17.14 seconds ("fair" category), and upper-body muscle strength averaged 31.56 repetitions. Meanwhile, the mean VO₂Max was 40.87 ± 3.37 ml/kg/min, with the majority of players (68.8%) falling into the "poor" category. These findings indicate that while the players possess adequate anaerobic performance capabilities to support explosive actions, they lack the aerobic capacity necessary to sustain match intensity throughout the game. Consequently, these results can serve as a foundation for developing a more targeted physical training program that emphasizes improving aerobic endurance through structured training, without neglecting the development of other physical fitness components.